Solving Airport Gate Allocation Problem Using Angle Modulated Simulated Kalman Filter - Kamil Zakwan, Mohd Azmi; Zulkifli, Md. Yusof; Siti Nurzulaikha, Satiman; Badaruddin, Muhammad; Saifudin, Razali; Zuwairie, Ibrahim; Nor Azlina, Ab. Aziz; Nor Hidayati, Abd Aziz (Universiti Malaysia Pahang, 2016)
In order to solve discrete optimization problem, the SKF algorithm is combined with angle modulated approach. Airport gate allocation problem refers to the search for optimal assignment of flights to gates at an airport. Assignment of flight to gates has become very complex nowadays, especially for a big size airport. In this study, the airport gate allocation problem is solved using a recently introduced angle modulated simulated Kalman filter (AMSKF). The objective of this study is to minimize the total walking distance. A small case study with 14 flights and 16 gates has been chosen. Preliminary results show that SKF is a promising algorithm for solving the airport gate allocation problem.